Urgensi Pengamalan Agama Bagi Remaja Muslim di Era Digital Melalui Media Sosial - Anam, Muhammad Syafi’i (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This article is motivated by the fact that the use of social media among teenagers nowadays is something that cannot be avoided anymore. Social media seems to be a new world for internet users to show themselves to other people. Moreover, currently there are many communication tools (gadgets) available at affordable prices that make it easier for users to access social media. This causes social media accounts to be owned by everyone. There is no need to deny that nowadays people seem more busy with their gadgets than with the situation around them. Almost every day teenagers access social media just to look for information via social media. The aim of this research is to provide education to Muslim teenagers to become a good generation through the practice of religion so that they are able to take advantage of all the conveniences offered in the digital era without having to abandon their identity as Islamic teenagers. The research method used is library research, namely by collecting data from writings (literacy) that are related to the topic discussed, namely the Urgency of Religious Practice for Muslim Youth in the Digital Era. The results of the research carried out are that current technology has brought major changes to the order of life. This progress can be utilized by all groups, both children and adults. Everything that used to be done manually is now done online, thus having a lot of positive impacts on life today. However, apart from the many positive impacts, the development of this technology also has negative impacts. To anticipate deviations and negative impacts, it is important to practice Islam for teenagers in the digital era..